2020
DOI: 10.1155/2020/9628957
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Short-Term Freeway Speed Prediction Based on Periodic Analysis Using Statistical Models and Machine Learning Models

Abstract: Accurate prediction of traffic information (i.e., traffic flow, travel time, traffic speed, etc.) is a key component of Intelligent Transportation System (ITS). Traffic speed is an important indicator to evaluate traffic efficiency. Up to date, although a few studies have considered the periodic feature in traffic prediction, very few studies comprehensively evaluate the impact of periodic component on statistical and machine learning prediction models. This paper selects several representative statistical mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
54
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(54 citation statements)
references
References 79 publications
0
54
0
Order By: Relevance
“…The accuracy can be further improved [ 31 ]. Considering the influence of the data interval, choosing an appropriate data interval is beneficial to improve the accuracy of the results [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The accuracy can be further improved [ 31 ]. Considering the influence of the data interval, choosing an appropriate data interval is beneficial to improve the accuracy of the results [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Time series data inevitably discuss cyclical and non-cyclical issues. The forecast for Freeway Speed focuses on the impact of periodicity on the forecast [ 27 ]. The prediction results of the six models in the article have been significantly improved after considering the cycle effects.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the characteristics of traffic flow have been discussed by some researchers when predicting short-term traffic flow. Zhang et al [31] and Yang et al [40] indicated that there is a periodic trend for traffic flow data. Hosseini et al [4] pointed out that the rules of traffic flow are different on weekdays/weekends.…”
Section: Table 1 Summarization Of Single Methods Applied For Short-tmentioning
confidence: 99%
“…In particular, (in)direct approximation using linear, multiple linear regression models and shallow neural networks are often encountered in practice. RNN and ARMA models are often adopted in research for traffic time series prediction [64,65]. Besides that, for most model types a 'simple' prediction application as well as a more sophisticated data fusion application is derived.…”
Section: Introduction Data Fusion Methodsmentioning
confidence: 99%